Estudo teórico das propriedades estruturais, eletrônicas e magnéticas da manganita hexagonal multiferróica LuMnO3 - Brito, Douglas Meneses Santos (2018)
In this work, was theoretically studied the structural, electronic and magnetic properties of multiferroic hexagonal manganite LuMnO3. For this compound, was simulated the crystal structure with P63cm and P63 crystallographic space group (CSG). Was employed the formalism of Density Functional Theory and the Full Potential Linearized Augmented Plane Wave (FP-LAPW) method implemented in Elk code. The exchange and correlation electronic effects were simulated by mean of LSDA. To better describe these effects, was employed the +U method (LSDA+U). Test with different +U method was performed. First, for both P63cm and P63 CSG, three collinear magnetic structures (ferromagnetic (FM), antiferromagnetic of type A (A-AFM) and of type G (G-AFM) were simulated. According to our results, the P63cm CSG with G-AFM state was found the most energetic favorable. This result was independent of either LSDA or LSDA+U method applied. In the second stage of the calculations, 2,3,4 and 3+4 non-collinear magnetic structures were performed. For these simulations, was employed only the LSDA scheme. Again, the P63cm CSG was found as the ground state for LuMnO3. Between the non-collinear magnetic structure simulated, the 3+4 was the lowest energy. For this magnetic structure, the band gap energy was underestimated (0.7 eV) in relation to experimental value (1.1 eV). However, the calculated spin magnetic (3.1uB) moment agree with experimental value (3.3 uB).